A method for recovering alkali in a dyeing and finishing plant
Patent Information
- Application Number
- CN202610875259.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-10-09
AI Technical Summary
单纯过滤或沉降只能去除较大颗粒和部分悬浮物,对溶解性染料、浆料和小分子有机助剂去除能力有限;混凝脱色容易引入新的无机盐和污泥,处理后的碱液纯度及回用稳定性不足;膜分离虽然具有一定分离效果,但染整废碱液中的胶体、染料和浆料容易造成膜污染、膜堵塞和通量衰减,清洗频繁,维护成本高;蒸发浓缩能耗较大,且若前端除杂不充分,浓缩过程中有机污染物会同步富集,影响回收碱液在后续工序中的使用效果;传统活性炭或普通吸附树脂在强碱环境下长期使用时容易出现吸附容量下降、再生效率不足或材料稳定性下降等问题
(1)本发明通过格栅、振动筛和多介质过滤器对染整废碱液进行前处理,能够先行去除染整废碱液中的粗大纤维、悬浮杂质、细小颗粒及部分胶体物质,降低后续固定床吸附柱的进水负荷,减少床层堵塞、沟流和压降升高等问题。多介质过滤器中填充石英砂、无烟煤和锰砂,可形成不同截留特性的过滤层,使预过滤后的染整废碱液更适合进入固定床吸附柱进行深度脱色除杂,从而提高碱回收过程的连续运行稳定性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of resource utilization technology for dyeing and finishing waste alkali liquor, specifically relating to a method for alkali recovery in dyeing and finishing workshops. Background Technology
[0002] In dyeing and finishing workshops, large quantities of alkali solutions are typically used during desizing, scouring, mercerizing, dyeing, and finishing processes. The resulting waste alkali solutions not only contain a certain amount of recyclable sodium hydroxide but also contain complex impurities such as fiber debris, sizing agents, dyes, surfactants, auxiliaries, oils and waxes, and colloidal suspended solids. These waste alkali solutions are usually highly alkaline, have high color intensity, high chemical oxygen demand (COD), and fluctuate significantly in composition. If directly introduced into a comprehensive wastewater treatment system, they would require a large amount of acid for neutralization, significantly increasing the load on subsequent coagulation, oxidation, biochemical treatment, and sludge disposal processes. This not only results in high operating costs but also wastes alkali resources. Therefore, purifying and recovering the effective alkali from dyeing and finishing waste alkali solutions is crucial for reducing alkali costs for dyeing and finishing enterprises, alleviating wastewater treatment pressure, and achieving resource recycling.
[0003] Existing methods for recovering and treating dyeing and finishing waste alkaline liquor mainly include sedimentation filtration, coagulation decolorization, membrane separation, evaporation concentration, activated carbon adsorption, resin adsorption, and combinations thereof. Simple filtration or sedimentation can only remove larger particles and some suspended solids, and has limited ability to remove soluble dyes, slurries, and small-molecule organic auxiliaries; coagulation decolorization easily introduces new inorganic salts and sludge, resulting in insufficient purity and reuse stability of the treated alkaline liquor; although membrane separation has a certain separation effect, colloids, dyes, and slurries in dyeing and finishing waste alkaline liquor easily cause membrane fouling, membrane blockage, and flux decline, requiring frequent cleaning and high maintenance costs; evaporation concentration consumes a lot of energy, and if the front-end impurity removal is insufficient, organic pollutants will accumulate simultaneously during the concentration process, affecting the utilization effect of the recovered alkaline liquor in subsequent processes; traditional activated carbon or ordinary adsorption resins are prone to problems such as decreased adsorption capacity, insufficient regeneration efficiency, or decreased material stability when used for a long time in a strongly alkaline environment.
[0004] Therefore, dyeing and finishing workshops urgently need a method suitable for strong alkaline systems, capable of continuously treating waste alkaline solutions, and possessing both decolorization, impurity removal, and alkali recovery capabilities. Ideal treatment materials should have a high specific surface area and a multi-level porous structure, effectively retaining dyes, colloids, slurries, and organic impurities, while not significantly losing effective sodium hydroxide in the waste alkaline solution; they should also have good alkali resistance and regeneration performance, allowing for repeated use in fixed-bed adsorption columns to reduce material replacement frequency. Summary of the Invention
[0005] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a method for alkali recovery in dyeing and finishing workshops.
[0006] A first aspect of the present invention provides a method for alkali recovery in a dyeing and finishing workshop, comprising the following steps: S1. The dyeing and finishing waste alkaline solution is filtered through a grid and a vibrating screen to obtain the filtered dyeing and finishing waste alkaline solution; the filtered dyeing and finishing waste alkaline solution is then filtered through a multi-media filter to obtain the pre-filtered dyeing and finishing waste alkaline solution. S2. The pre-filtered dyeing and finishing waste alkaline liquid is pumped into a fixed bed adsorption column filled with cerium-based metal-organic framework-derived cerium-oxygen clusters supported on niobate-functionalized mesoporous titanium dioxide composite nanosheets. The pre-filtered dyeing and finishing waste alkaline liquid enters from the top of the fixed bed adsorption column and flows out from the bottom, thus obtaining the recovered alkaline liquid after adsorption treatment. S3. When the color of the effluent from the fixed bed adsorption column is greater than 30 degrees or the COD removal rate drops to below 85% of the initial COD removal rate, stop feeding the pre-filtered dyeing and finishing waste alkaline solution; first, rinse the fixed bed adsorption column with clean water in a reverse direction, then desorb it with a 2-5% sodium hydroxide solution at 50-60℃; finally, rinse the fixed bed adsorption column with clean water. S4. Measure the sodium hydroxide concentration in the recovered alkali solution after adsorption treatment. If the sodium hydroxide concentration is lower than the target process requirement, the recovered alkali solution is concentrated by negative pressure evaporation to obtain the adjusted recovered alkali solution. If the sodium hydroxide concentration is higher than the target process requirement, the recovered alkali solution is diluted to obtain the adjusted recovered alkali solution.
[0007] In this invention, during the alkali recovery process in the dyeing and finishing workshop, the waste alkali solution is first filtered through a grid and a vibrating screen, where larger fibers, fabric scraps, and suspended impurities are retained. It then enters a multi-media filter filled with quartz sand, anthracite, and manganese sand, where fine suspended solids, colloidal particles, and some inorganic impurities are further retained by the filter layer, resulting in pre-filtered waste alkali solution. This reduces clogging of the fixed-bed adsorption column and increases bed pressure drop. After activation in a vacuum drying oven, the cerium-based metal-organic framework-derived cerium-oxygen cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets exhibit reduced residual moisture and low-boiling-point solvents within the pores, making it easier for surface sites to contact contaminants in the waste alkali solution. The pre-filtered dyeing and finishing waste alkaline solution enters from the top of the fixed-bed adsorption column and flows out from the bottom. Water and sodium hydroxide flow through the bed with the liquid and form the recovered alkaline solution after adsorption treatment. Dyes, slurries, colloids, fiber degradation products, surfactants, and other organic impurities are jointly retained by the mesoporous channels, cerium oxygen cluster sites, niobate functionalization sites, and titanium dioxide surface of the cerium-based metal-organic framework-derived cerium oxygen cluster-loaded niobate functionalized mesoporous titanium dioxide composite nanosheets. The cerium oxygen clusters provide polar metal oxygen sites, and the niobate functionalized mesoporous titanium dioxide nanosheets provide an alkali-resistant inorganic framework, pore mass transfer pathways, and surface hydroxyl sites, enabling the material to possess adsorption, retention, and mass transfer capabilities. When the effluent color of the fixed-bed adsorption column increases or the removal capacity of organic pollutants decreases, it indicates that the adsorption sites of the bed are close to saturation. After stopping the liquid feed, backwashing with clean water can remove loose particles in the bed gaps and restore the channels to open. When sodium hydroxide solution is heated for desorption, it can weaken the interaction between dyes and organic impurities and the surface of cerium-based metal-organic framework-derived cerium oxide clusters supported on niobate-functionalized mesoporous titanium dioxide composite nanosheets, causing them to migrate from the pores and surface into the desorption solution. Subsequently, the fixed-bed adsorption column is rinsed with clean water to reduce residual desorption solution and restore the adsorption capacity of the bed. After the adsorption treatment, the recovered alkali solution is concentrated or diluted by negative pressure evaporation according to the requirements of the target process after sodium hydroxide concentration determination, to obtain a conditioned recovered alkali solution that can be reused in the mercerizing, scouring, or dyeing processes.
[0008] According to a preferred embodiment of the present invention, in step S1, the multi-media filter is filled with quartz sand, anthracite, and manganese sand.
[0009] According to a preferred embodiment of the present invention, in step S2, the cerium-based metal-organic framework-derived cerium-oxygen cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets are activated in a vacuum drying oven at 80-100°C for 4-8 hours, and then packed into a fixed-bed adsorption column.
[0010] According to a preferred embodiment of the present invention, in step S3, the desorption time is 60-120 min.
[0011] According to a preferred embodiment of the present invention, in step S3, after desorption, the fixed bed adsorption column is rinsed with clean water for 30-60 minutes.
[0012] According to a preferred embodiment of the present invention, the preparation steps of the cerium-based metal-organic framework-derived cerium oxide cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets include: A1. By weight, under nitrogen protection, mix 10-15 parts of cerium nitrate hexahydrate, 120-180 parts of N,N-dimethylformamide, and 40-70 parts of glacial acetic acid, and stir at room temperature to obtain a cerium-containing precursor solution; mix 5.5-9.5 parts of 2,2′-bipyridine-5,5′-dicarboxylic acid, 60-100 parts of N,N-dimethylformamide, and 20-40 parts of glacial acetic acid, and stir at room temperature to obtain a ligand dispersion; add the ligand dispersion dropwise to the cerium-containing precursor solution, and continue stirring at room temperature to obtain a premix; A2. Transfer the premixed solution to an autoclave and stir. After sealing the autoclave, heat it to 120-135℃ for reaction, and then cool it naturally to room temperature to obtain the reaction product. Centrifuge the reaction product to obtain the precipitate. Wash the precipitate sequentially with N,N-dimethylformamide, anhydrous ethanol and deionized water, and vacuum dry it to obtain the cerium-based metal-organic framework material. A3. Mix 2.0-4.0 parts of P123 and 80-120 parts of anhydrous ethanol and stir; add 3-8 parts of hydrochloric acid solution to adjust the pH to 1.5-2.5; add 15-25 parts of tetrabutyl titanate and stir to obtain titanium sol; dissolve 1.0-3.0 parts of ammonium niobate oxalate in 20-40 parts of deionized water to obtain niobium source solution; add the niobium source solution to the titanium sol and stir to obtain mixed sol; transfer the mixed sol to an autoclave, heat to 140-170℃ for reaction, and then cool naturally to room temperature to obtain reaction product; centrifuge the reaction product to obtain precipitate; wash the precipitate successively with deionized water and anhydrous ethanol, vacuum dry, and calcine in air at 400-500℃ to obtain niobate-functionalized mesoporous titanium dioxide nanosheets; A4. Mix 5-10 parts of cerium-based metal-organic framework material, 10-30 parts of niobate-functionalized mesoporous titanium dioxide nanosheets, and 150-250 parts of anhydrous ethanol, stir at room temperature, and ultrasonically disperse. Add 0.5-1.5 parts of 3-aminopropyltriethoxysilane and 1-7.5 parts of deionized water, and reflux at 75-85℃ to obtain the reaction product. Centrifuge the reaction product to obtain a solid product. Wash the solid product sequentially with anhydrous ethanol and deionized water, and vacuum dry to obtain a vacuum-dried solid product. Place the vacuum-dried solid product in a tube furnace and heat-treat at 400-500℃ under a nitrogen atmosphere. Allow to cool naturally to room temperature.
[0013] In this invention, the formation of cerium-based metal-organic framework-derived cerium-oxygen cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets originates from the separate construction of a cerium coordination framework and a mesoporous titanium-oxygen framework. After cerium nitrate hexahydrate enters the system composed of N,N-dimethylformamide and glacial acetic acid, cerium ions are fully dispersed. Glacial acetic acid, through its carboxyl groups, competes with cerium ions for coordination, regulating the coordination balance around the cerium ions, reducing the instantaneous nucleation rate, and making the subsequent crystallization process more uniform. After 2,2′-bipyridine-5,5′-dicarboxylic acid is added to N,N-dimethylformamide and glacial acetic acid to form a ligand dispersion, it is mixed with a cerium-containing precursor solution. The carboxyl groups of 2,2′-bipyridine-5,5′-dicarboxylic acid gradually replace the coordination sites of glacial acetic acid and coordinate with cerium ions, forming a premix. After the premixed solution was transferred to an autoclave, a solvothermal reaction was carried out in a closed environment. Cerium ions further nucleated and crystallized with the carboxyl groups of 2,2′-bipyridine-5,5′-dicarboxylic acid. The cerium centers formed polynuclear cluster nodes by bridging oxygen and were connected by carboxyl groups, constructing an ordered cerium-based metal-organic framework material. The bipyridine nitrogen atoms in 2,2′-bipyridine-5,5′-dicarboxylic acid were retained as open sites within the framework. In another part of the reaction, P123 underwent micelle self-assembly in an acidic alcohol system composed of anhydrous ethanol and hydrochloric acid solution through differential dissolution of hydrophobic and hydrophilic segments. After the addition of tetrabutyl titanate, the hydrolysis and condensation were controlled under acidic conditions, and titanium oxide species gradually condensed around the P123 micelles to form a titanium sol. Niobium ammonium oxalate was dissolved in deionized water and added to the titanium sol. Niobium oxide species entered the framework or distributed on the surface during the hydrolysis and condensation process of the titanium oxide network, forming a mixed sol. After the mixed sol is reacted in an autoclave, the titanium-oxygen framework continues to condense and form a mesoporous structure. Following washing, vacuum drying, and calcination in air, P123 is removed, and the titanium-oxygen framework is fixed, yielding niobate-functionalized mesoporous titanium dioxide nanosheets. After dispersing the cerium-based metal-organic framework material and the niobate-functionalized mesoporous titanium dioxide nanosheets in anhydrous ethanol, 3-aminopropyltriethoxysilane hydrolyzes in deionized water to generate silanol groups, which condense with the hydroxyl groups on the surface of the niobate-functionalized mesoporous titanium dioxide nanosheets to form titanium-oxygen-silicon bonds. This promotes the contact and interfacial bonding between the cerium-based metal-organic framework material and the niobate-functionalized mesoporous titanium dioxide nanosheets during the composite stage. After heat treatment in a nitrogen atmosphere, the organic ligands in the cerium-based metal-organic framework material undergo thermal conversion and removal. The cerium centers are transformed into dispersed cerium-oxygen clusters and anchored on the surface of the niobate-functionalized mesoporous titanium dioxide nanosheets, forming cerium-based metal-organic framework-derived cerium-oxygen cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets.
[0014] According to a preferred embodiment of the present invention, in step A1, after the ligand dispersion is added dropwise to the cerium-containing precursor solution, the stirring is continued at room temperature for 6-8 hours.
[0015] According to a preferred embodiment of the present invention, in step A2, the reaction time at 120-135°C is 36-48 hours.
[0016] According to a preferred embodiment of the present invention, in step A3, the reaction time at 140-170°C is 24-36 hours.
[0017] According to a preferred embodiment of the present invention, in step A4, the reflux reaction time at 75-85°C is 12-18 hours.
[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention pretreats dyeing and finishing waste alkaline solution using a grid, vibrating screen, and multi-media filter. This pretreats coarse fibers, suspended impurities, fine particles, and some colloidal substances from the waste alkaline solution, reducing the influent load of the subsequent fixed-bed adsorption column and minimizing problems such as bed blockage, channeling, and increased pressure drop. The multi-media filter is filled with quartz sand, anthracite, and manganese sand, which can form filter layers with different retention characteristics. This makes the pre-filtered dyeing and finishing waste alkaline solution more suitable for entering the fixed-bed adsorption column for deep decolorization and impurity removal, thereby improving the continuous operation stability of the alkali recovery process.
[0019] (2) This invention uses cerium-based metal-organic framework-derived cerium oxide clusters supported on niobate-functionalized mesoporous titanium dioxide composite nanosheets as the functional material in a fixed-bed adsorption column. After activation in a vacuum drying oven, the pore structure and surface interaction sites of this material make it easier to contact impurities such as dyes, slurries, colloids, fiber degradation products, and surfactants in dyeing and finishing waste alkaline solutions. The cerium oxide clusters, niobate-functionalized mesoporous titanium dioxide nanosheets, and mesoporous channels in the cerium-based metal-organic framework-derived cerium oxide clusters supported on niobate-functionalized mesoporous titanium dioxide composite nanosheets form a synergistic effect, which can not only improve the impurity retention and adsorption capacity, but also allow water and sodium hydroxide to pass through the bed with the liquid flow, thereby obtaining the recovered alkaline solution after adsorption treatment and reducing the loss of effective alkali.
[0020] (3) In this invention, when the effluent color of the fixed-bed adsorption column increases or the removal capacity of organic pollutants decreases, a regeneration method combining reverse rinsing with clean water, desorption with sodium hydroxide solution, and rinsing with clean water is adopted. This releases and removes impurities adsorbed on the surface and pores of cerium-based metal-organic framework-derived cerium oxide cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets, allowing the fixed-bed adsorption column to regain its processing capacity. After the adsorption treatment, the recovered alkali solution is concentrated or diluted by negative pressure evaporation after sodium hydroxide concentration determination to obtain an adjusted recovered alkali solution, which is convenient for reuse in the dyeing and finishing production process, reducing the consumption of new alkali and the treatment load of dyeing and finishing waste alkali solution. Detailed Implementation
[0021] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0022] Example 1 This embodiment provides a method for alkali recovery in a dyeing and finishing workshop, including the following steps: S1. Take 50,000g of dyeing and finishing waste alkali solution, filter it first through a grid with a grid gap of 2mm, and then filter it through a vibrating screen with a screen aperture of 0.5mm to obtain the filtered dyeing and finishing waste alkali solution; filter the filtered dyeing and finishing waste alkali solution through a multi-media filter, which is filled from top to bottom with 300g of anthracite, 500g of quartz sand and 200g of manganese sand, and the filtration flow rate is controlled at 3L / h to obtain the pre-filtered dyeing and finishing waste alkali solution.
[0023] S2. 500g of cerium-based metal-organic framework-derived cerium-oxygen cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets were placed in a 90℃ vacuum drying oven and activated for 6h under a vacuum of -0.09MPa. Then, they were packed into a fixed-bed adsorption column with an inner diameter of 50mm and a height of 600mm. The packing height of the cerium-based metal-organic framework-derived cerium-oxygen cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets was 400mm. After packing, the fixed-bed adsorption column was pre-washed with 3000g of deionized water, which entered from the top and flowed out from the bottom. The pre-filtered dyeing and finishing waste alkali solution was pumped into the fixed-bed adsorption column with the liquid entering from the top and flowing out from the bottom at a flow rate of 2L / h to obtain the recovered alkali solution after adsorption treatment.
[0024] S3. Continuously monitor the effluent from the fixed-bed adsorption column. When the effluent color exceeds 30 degrees or the COD removal rate drops below 85% of the initial COD removal rate, stop feeding the pre-filtered dyeing and finishing waste alkaline solution. First, use 5000g of clean water to perform a reverse flushing from the bottom to the top of the fixed-bed adsorption column at a flow rate of 2L / h. Then, use 8000g of 3.5% sodium hydroxide solution at 55℃ for desorption. The desorption solution enters from the top and exits from the bottom of the fixed-bed adsorption column at a flow rate of 2L / h and a desorption time of 90min. Finally, use 6000g of clean water to flush the fixed-bed adsorption column at a flow rate of 2L / h and a flushing time of 45min.
[0025] S4. Measure the sodium hydroxide concentration in the recovered alkali solution after adsorption treatment. If the sodium hydroxide concentration is lower than the target process requirement, transfer the recovered alkali solution to a negative pressure evaporation device and concentrate it under negative pressure evaporation at 60℃ and -0.08MPa to obtain the adjusted recovered alkali solution. If the sodium hydroxide concentration is higher than the target process requirement, add deionized water to dilute the recovered alkali solution and stir evenly to obtain the adjusted recovered alkali solution.
[0026] Preparation steps of cerium-based metal-organic framework-derived cerium-oxygen cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets: A1. Under nitrogen protection, 12.5 g of cerium nitrate hexahydrate, 150 g of N,N-dimethylformamide, and 55 g of glacial acetic acid were added to a glass reactor. The room temperature was controlled at 25 °C, and the mixture was stirred at 300 r / min for 30 min to obtain a cerium-containing precursor solution. 7.5 g of 2,2′-bipyridine-5,5′-dicarboxylic acid, 80 g of N,N-dimethylformamide, and 30 g of glacial acetic acid were added to another 500 mL glass reactor. The room temperature was controlled at 25 °C, and the mixture was stirred at 300 r / min for 60 min to obtain a ligand dispersion. The ligand dispersion was added dropwise to the cerium-containing precursor solution at a rate of 2 mL / min. During the addition, nitrogen protection was maintained, and the mixture was stirred at 350 r / min. After the addition was completed, stirring was continued at 25 °C for 7 h to obtain a premixed solution.
[0027] A2. Transfer the premixed solution to a polytetrafluoroethylene-lined autoclave, controlling the liquid volume to be 70% of the liner volume. Stir at 300 r / min for 10 min, then seal. Place the autoclave in an oven and heat to 127.5℃ for 42 h, then allow it to cool naturally to 25℃ to obtain the reaction product. Centrifuge the reaction product at 7000 r / min for 8 min to obtain the precipitate. Wash the precipitate sequentially with 100 g N,N-dimethylformamide, 100 g anhydrous ethanol, and 100 g deionized water, three times with each washing solution. After each washing, centrifuge at 7000 r / min for 8 min. Then place the washed precipitate in a 70℃ vacuum drying oven and dry it under a vacuum of -0.09 MPa for 12 h to obtain the cerium-based metal-organic framework material.
[0028] A3. Add 3.0 g P123 and 100 g anhydrous ethanol to a glass reactor and stir at 400 r / min for 60 min at 25 °C. Add 5.5 g hydrochloric acid solution to adjust the pH to 2.0. Add 20 g tetrabutyl titanate dropwise to the above system at a rate of 1 mL / min, maintaining stirring at 400 r / min during the addition. After the addition is complete, continue stirring for 60 min to obtain a titanium sol. Dissolve 2.0 g ammonium niobate oxalate in 30 g deionized water and stir at 300 r / min for 30 min at 25 °C to obtain a niobium source solution. Add the niobium source solution to the titanium sol at a rate of 1 mL / min, maintaining stirring at 400 r / min during the addition. After the addition is complete, continue stirring for 60 min to obtain a mixed solution. The mixed sol was transferred to a 300 mL polytetrafluoroethylene-lined autoclave, with the liquid volume controlled to be 70% of the liner volume. After sealing, the mixture was heated to 155 °C and reacted for 30 h, followed by natural cooling to 25 °C to obtain the reaction product. The reaction product was centrifuged at 7000 r / min for 8 min to obtain the precipitate. The precipitate was washed successively with 100 g deionized water and 100 g anhydrous ethanol, three times with each washing solution. After each washing, the precipitate was centrifuged at 7000 r / min for 8 min, and then placed in an 80 °C vacuum drying oven and dried at a vacuum of -0.09 MPa for 12 h. The precipitate was then placed in a muffle furnace and calcined at 450 °C in air atmosphere for 3 h, followed by natural cooling to 25 °C to obtain niobate-functionalized mesoporous titanium dioxide nanosheets.
[0029] A4. 7.5g of cerium-based metal-organic framework material, 20g of niobate-functionalized mesoporous titanium dioxide nanosheets, and 200g of anhydrous ethanol were added to a glass reactor. The mixture was stirred at 400r / min for 60min at 25℃, and then ultrasonically dispersed at 300W for 30min to obtain a homogeneous dispersion. 1.0g of 3-aminopropyltriethoxysilane and 4.25g of deionized water were added to the homogeneous dispersion. The temperature was raised to 80℃, and the mixture was stirred at 400r / min under reflux for 15h to obtain the reaction product. The reaction product was centrifuged at 7000r / min for 8min to obtain a solid product. The solid product was washed sequentially with 100g of anhydrous ethanol and 100g of deionized water, three times with each washing solution. After each washing, it was centrifuged at 7000r / min for 8min and then placed in a vacuum drying oven at 70℃ and dried at a vacuum of -0.09MPa for 12h to obtain the vacuum-dried solid product. The vacuum-dried solid product was placed in a tube furnace and heat-treated at 450℃ for 3h under a nitrogen atmosphere. After the heat treatment, it was naturally cooled to 25℃ under a nitrogen atmosphere to obtain cerium-based metal-organic framework-derived cerium oxide cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets.
[0030] Example 2 The difference between this embodiment and Embodiment 1 is that this embodiment provides a method for alkali recovery in a dyeing and finishing workshop, including the following steps: S1. Take 50,000g of dyeing and finishing waste alkali solution, filter the waste alkali solution through a grid first, and then filter it through a vibrating screen to obtain filtered dyeing and finishing waste alkali solution; filter the filtered dyeing and finishing waste alkali solution through a multi-media filter, the multi-media filter being filled with 500g of quartz sand, 300g of anthracite and 200g of manganese sand to obtain pre-filtered dyeing and finishing waste alkali solution.
[0031] S2. 500g of cerium-based metal-organic framework-derived cerium-oxygen cluster-supported niobate functionalized mesoporous titanium dioxide composite nanosheets were activated in an 80℃ vacuum drying oven for 4h, and then packed into a fixed-bed adsorption column. The pre-filtered dyeing and finishing waste alkali liquid was pumped into the fixed-bed adsorption column. The pre-filtered dyeing and finishing waste alkali liquid entered from the top of the fixed-bed adsorption column and flowed out from the bottom to obtain the recovered alkali liquid after adsorption treatment.
[0032] S3. When the effluent color of the fixed-bed adsorption column is greater than 30 degrees or the COD removal rate drops to below 85% of the initial COD removal rate, stop feeding the pre-filtered dyeing and finishing waste alkaline solution; first, rinse the fixed-bed adsorption column with 5000g of clean water in a reverse direction, then desorb with 8000g of 2% sodium hydroxide solution at 50℃ for 60min; finally, rinse the fixed-bed adsorption column with 6000g of clean water for 30min.
[0033] S4. Measure the sodium hydroxide concentration in the recovered alkali solution after adsorption treatment. If the sodium hydroxide concentration is lower than the target process requirement, the recovered alkali solution is concentrated by negative pressure evaporation to obtain the adjusted recovered alkali solution. If the sodium hydroxide concentration is higher than the target process requirement, deionized water is added to dilute the recovered alkali solution to obtain the adjusted recovered alkali solution.
[0034] Preparation steps of cerium-based metal-organic framework-derived cerium-oxygen cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets: A1. Under nitrogen protection, 10g of cerium nitrate hexahydrate, 120g of N,N-dimethylformamide, and 40g of glacial acetic acid were added to a clean reactor and mixed. The mixture was stirred at room temperature until the cerium nitrate hexahydrate was fully dispersed to obtain a cerium-containing precursor solution. 5.5g of 2,2′-bipyridine-5,5′-dicarboxylic acid, 60g of N,N-dimethylformamide, and 20g of glacial acetic acid were added to another clean reactor and mixed. The mixture was stirred at room temperature until a uniform dispersion system was formed to obtain a ligand dispersion. The ligand dispersion was slowly added dropwise to the cerium-containing precursor solution while maintaining nitrogen protection during the addition. After the addition was completed, the mixture was stirred at room temperature for 6 hours to obtain a premixed solution.
[0035] A2. Transfer the premixed solution to an autoclave, stir evenly, seal, heat the autoclave to 120℃ and react for 36 hours, then cool naturally to room temperature to obtain the reaction product; centrifuge the reaction product to obtain the precipitate; wash the precipitate sequentially with N,N-dimethylformamide, anhydrous ethanol and deionized water until the washing solution is clear, then vacuum dry to obtain the cerium-based metal-organic framework material.
[0036] A3. Add 2.0g of P123 and 80g of anhydrous ethanol to the reactor and mix, stirring until P123 is fully dispersed; add 3g of hydrochloric acid solution to adjust the pH to 1.5; add 15g of tetrabutyl titanate dropwise to the system while stirring during the dropwise addition, and continue stirring after the dropwise addition is complete to obtain titanium sol; dissolve 1.0g of ammonium niobate oxalate in 20g of deionized water to obtain a niobium source solution; add the niobium source solution to the titanium sol and stir until the system is homogeneous to obtain a mixed sol; transfer the mixed sol to an autoclave, seal it, and heat it to 140℃ for 24h, then cool it naturally to room temperature to obtain the reaction product; centrifuge the reaction product to obtain the precipitate; wash the precipitate successively with deionized water and anhydrous ethanol, then vacuum dry it, and then calcine it at 400℃ in an air atmosphere to obtain niobate-functionalized mesoporous titanium dioxide nanosheets.
[0037] A4. 5g of cerium-based metal-organic framework material, 10g of niobate-functionalized mesoporous titanium dioxide nanosheets, and 150g of anhydrous ethanol were added to a reactor and mixed. The mixture was stirred and ultrasonically dispersed at room temperature to ensure uniform suspension of the solid material. 0.5g of 3-aminopropyltriethoxysilane and 1g of deionized water were added, and the mixture was heated to 75℃ and refluxed for 12h to obtain the reaction product. The reaction product was centrifuged to obtain a solid product. The solid product was washed sequentially with anhydrous ethanol and deionized water, and then vacuum dried to obtain a vacuum-dried solid product. The vacuum-dried solid product was placed in a tube furnace and heat-treated at 400℃ under a nitrogen atmosphere, then naturally cooled to room temperature to obtain cerium-based metal-organic framework-derived cerium oxide cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets.
[0038] Example 3 The difference between this embodiment and Embodiment 1 is that this embodiment provides a method for alkali recovery in a dyeing and finishing workshop, including the following steps: S1. Take 50,000g of dyeing and finishing waste alkali solution, filter the waste alkali solution through a grid first, and then filter it through a vibrating screen to obtain filtered dyeing and finishing waste alkali solution; filter the filtered dyeing and finishing waste alkali solution through a multi-media filter, the multi-media filter being filled with 500g of quartz sand, 300g of anthracite and 200g of manganese sand to obtain pre-filtered dyeing and finishing waste alkali solution.
[0039] S2. 500g of cerium-based metal-organic framework-derived cerium-oxygen cluster-supported niobate functionalized mesoporous titanium dioxide composite nanosheets were activated in a vacuum drying oven at 100℃ for 8h, and then packed into a fixed-bed adsorption column. The pre-filtered dyeing and finishing waste alkali solution was pumped into the fixed-bed adsorption column. The pre-filtered dyeing and finishing waste alkali solution entered from the top of the fixed-bed adsorption column and flowed out from the bottom to obtain the recovered alkali solution after adsorption treatment.
[0040] S3. When the effluent color of the fixed-bed adsorption column is greater than 30 degrees or the COD removal rate drops to below 85% of the initial COD removal rate, stop feeding the pre-filtered dyeing and finishing waste alkaline solution; first, rinse the fixed-bed adsorption column with 5000g of clean water in a reverse direction, then desorb with 8000g of 5% sodium hydroxide solution at 60℃ for 120min; finally, rinse the fixed-bed adsorption column with 6000g of clean water for 60min.
[0041] S4. Measure the sodium hydroxide concentration in the recovered alkali solution after adsorption treatment. If the sodium hydroxide concentration is lower than the target process requirement, the recovered alkali solution is concentrated by negative pressure evaporation to obtain the adjusted recovered alkali solution. If the sodium hydroxide concentration is higher than the target process requirement, deionized water is added to dilute the recovered alkali solution to obtain the adjusted recovered alkali solution.
[0042] Preparation steps of cerium-based metal-organic framework-derived cerium-oxygen cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets: A1. Under nitrogen protection, 15g of cerium nitrate hexahydrate, 180g of N,N-dimethylformamide, and 70g of glacial acetic acid were added to a clean reactor and mixed. The mixture was stirred at room temperature until the cerium nitrate hexahydrate was fully dispersed to obtain a cerium-containing precursor solution. 9.5g of 2,2′-bipyridine-5,5′-dicarboxylic acid, 100g of N,N-dimethylformamide, and 40g of glacial acetic acid were added to another clean reactor and mixed. The mixture was stirred at room temperature until a uniform dispersion system was formed to obtain a ligand dispersion. The ligand dispersion was slowly added dropwise to the cerium-containing precursor solution while maintaining nitrogen protection during the addition. After the addition was completed, the mixture was stirred at room temperature for 8 hours to obtain a premixed solution.
[0043] A2. Transfer the premixed solution to an autoclave, stir evenly, seal, heat the autoclave to 135℃ and react for 48 hours, then cool naturally to room temperature to obtain the reaction product; centrifuge the reaction product to obtain the precipitate; wash the precipitate sequentially with N,N-dimethylformamide, anhydrous ethanol and deionized water until the washing solution is clear, then vacuum dry to obtain the cerium-based metal-organic framework material.
[0044] A3. Add 4.0g of P123 and 120g of anhydrous ethanol to the reactor and mix, stirring until P123 is fully dispersed; add 8g of hydrochloric acid solution to adjust the pH to 2.5; add 25g of tetrabutyl titanate dropwise to the system while stirring during the dropwise addition, and continue stirring after the dropwise addition is complete to obtain titanium sol; dissolve 3.0g of ammonium niobate oxalate in 40g of deionized water to obtain a niobium source solution; add the niobium source solution to the titanium sol and stir until the system is homogeneous to obtain a mixed sol; transfer the mixed sol to an autoclave, seal it, and heat it to 170℃ for 36h, then cool it naturally to room temperature to obtain the reaction product; centrifuge the reaction product to obtain the precipitate; wash the precipitate successively with deionized water and anhydrous ethanol, then vacuum dry it, and then calcine it at 500℃ in an air atmosphere to obtain niobate-functionalized mesoporous titanium dioxide nanosheets.
[0045] A4. 10g of cerium-based metal-organic framework material, 30g of niobate-functionalized mesoporous titanium dioxide nanosheets, and 250g of anhydrous ethanol were added to a reactor and mixed. The mixture was stirred and ultrasonically dispersed at room temperature to ensure uniform suspension of the solid material. 1.5g of 3-aminopropyltriethoxysilane and 7.5g of deionized water were added, and the mixture was heated to 85℃ and refluxed for 18h to obtain the reaction product. The reaction product was centrifuged to obtain a solid product. The solid product was washed sequentially with anhydrous ethanol and deionized water, and then vacuum dried to obtain a vacuum-dried solid product. The vacuum-dried solid product was placed in a tube furnace and heat-treated at 500℃ under a nitrogen atmosphere, then naturally cooled to room temperature to obtain cerium-based metal-organic framework-derived cerium oxide cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets.
[0046] Comparative Example 1 The difference between this comparative example and Example 1 is that no cerium-based metal-organic framework material was prepared, and 7.5g of cerium-based metal-organic framework material was not added. Otherwise, it is exactly the same as Example 1.
[0047] Comparative Example 2 The difference between this comparative example and Example 1 is that niobate-functionalized mesoporous titanium dioxide nanosheets are not prepared, and 20g of niobate-functionalized mesoporous titanium dioxide nanosheets are not added; otherwise, it is exactly the same as Example 1.
[0048] Comparative Example 3 The difference between this comparative example and Example 1 is that 1.0 g of 3-aminopropyltriethoxysilane is not added in step A4, but otherwise it is exactly the same as Example 1.
[0049] In accordance with national and industry standard testing specifications, a series of standardized tests were conducted on the alkali recovery methods in dyeing and finishing workshops described in Examples 1-3 and Comparative Examples 1-3.
[0050] The dyeing and finishing waste alkaline solution continuously discharged from the same dyeing and finishing workshop was taken as the test object. First, it was stirred in an alkali-resistant storage tank at 100 r / min for 30 min to make the dye, sizing agent, colloid and suspended impurities in the dyeing and finishing waste alkaline solution evenly distributed. Then it was divided into 6 groups, each with 50,000 g, and treated according to the methods of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 respectively.
[0051] Before treatment, 100 mL of sample was taken from each group of dyeing and finishing waste alkaline solution to determine the initial sodium hydroxide concentration, initial color, and initial COD. After treatment, the recovered alkaline solution after adsorption treatment was collected from the outlet of the fixed bed adsorption column. When the color of the water effluent from the fixed bed adsorption column was greater than 30 degrees or the COD removal rate dropped to below 85% of the initial COD removal rate, the feeding of the pre-filtered dyeing and finishing waste alkaline solution was stopped. The cumulative mass of the recovered alkaline solution obtained after adsorption treatment for this group was weighed and recorded as the cumulative mass of the single treatment solution, in g.
[0052] During the alkali recovery rate test, accurately weigh 10.00 g of the untreated dyeing and finishing waste alkali solution and 10.00 g of the recovered alkali solution after adsorption treatment. Dilute each solution with deionized water to 100 mL, add phenolphthalein indicator, and titrate with a standardized hydrochloric acid solution until the solution changes from red to colorless and remains colorless for 30 s. Calculate the sodium hydroxide concentration in the untreated dyeing and finishing waste alkali solution and the recovered alkali solution after adsorption treatment based on the volume of hydrochloric acid standard solution consumed. Then calculate the alkali recovery rate as a percentage of the total mass of sodium hydroxide in the recovered alkali solution after adsorption treatment to the total mass of sodium hydroxide in the untreated dyeing and finishing waste alkali solution. The unit is .
[0053] During the color removal rate test, 50 mL of dyeing and finishing waste alkali solution before treatment and 50 mL of recovered alkali solution after adsorption treatment were taken respectively. The color was measured by the dilution factor method. The color removal rate was calculated as the percentage of the difference between the color before treatment and the color after treatment to the color before treatment. The unit is .
[0054] During the COD removal rate test, 10 mL of dyeing and finishing waste alkaline solution before treatment and 10 mL of recovered alkaline solution after adsorption treatment were taken respectively. After digestion, cooling and titration, the COD was calculated. The COD removal rate was calculated as the percentage of the difference between the COD before treatment and the COD after treatment to the COD before treatment. The unit is 0.
[0055] During the pressure drop test of the fixed-bed adsorption column, alkali-resistant pressure gauges are set at the inlet and outlet of the fixed-bed adsorption column. After the fixed-bed adsorption column has been running stably for 30 minutes, the inlet pressure and outlet pressure are read. The difference between the two is recorded as the pressure drop of the fixed-bed adsorption column, and the unit is kPa.
[0056] After the 10th cycle, when the alkali recovery rate test was conducted, after each fixed bed adsorption column reached the stop liquid feeding condition, it was rinsed with clean water, desorbed with sodium hydroxide solution, and rinsed with clean water according to the corresponding embodiment or comparative example to complete one adsorption regeneration cycle. After 10 consecutive cycles, the same batch of dyeing and finishing waste alkali solution was treated again, and the alkali recovery rate after the 10th cycle was calculated according to the above alkali recovery rate test method, in units of .
[0057] The performance test data above are shown in Table 1.
[0058] Table 1 Performance Test Results As can be seen from the above, Examples 1-3 can more effectively solve the problems of insufficient alkali resource recovery rate, weak dye and organic impurity removal capacity, low fixed bed processing capacity, high operating resistance, and significant performance degradation after recycling compared to Comparative Examples 1-3.
[0059] The alkali recovery rates of Examples 1-3 were 94.6%, 91.8%, and 93.2%, respectively, which were significantly higher than those of Comparative Example 1 (86.7%), Comparative Example 2 (82.5%), and Comparative Example 3 (88.9%). This indicates that the combined action of cerium-based metal-organic framework-derived cerium-oxygen clusters, niobate-functionalized mesoporous titanium dioxide nanosheets, and 3-aminopropyltriethoxysilane interface treatment can reduce the loss of sodium hydroxide due to impurity retention or regeneration while adsorbing dyes, slurries, and colloidal impurities, thus maintaining a high effective alkali content in the recovered alkali solution after adsorption treatment.
[0060] The color removal rates of Examples 1-3 were 93.5%, 89.4%, and 91.6%, respectively, which were significantly higher than those of Comparative Example 1 (76.8%), Comparative Example 2 (69.5%), and Comparative Example 3 (81.2%). This indicates that when only niobate-functionalized mesoporous titanium dioxide nanosheets or only cerium-based metal-organic framework materials are retained, the adsorption and retention capacity for dye molecules is insufficient. Furthermore, when the 3-aminopropyltriethoxysilane interface treatment is lacking, the dispersion and binding of the two types of functional components (niobate-functionalized mesoporous titanium dioxide nanosheets and cerium-based metal-organic framework materials) are insufficient, and the decolorization capacity is also significantly reduced.
[0061] The COD removal rates of Examples 1-3 were 80.8%, 74.6%, and 78.2%, respectively, which were higher than those of Comparative Example 1 (61.4%), Comparative Example 2 (55.7%), and Comparative Example 3 (66.9%). This indicates that cerium-based metal-organic framework-derived cerium oxide clusters supported on niobate-functionalized mesoporous titanium dioxide composite nanosheets have a synergistic removal effect on slurry, surfactants, fiber degradation products, and other organic impurities in dyeing and finishing waste alkaline solution, and can reduce the organic pollution load in the recovered alkaline solution.
[0062] In terms of the cumulative mass of the liquid treated in a single batch, Examples 1-3 reached 46200g, 43800g and 45100g respectively, which are significantly higher than Comparative Example 1 (37100g), Comparative Example 2 (34800g) and Comparative Example 3 (39600g), indicating that the complete composite material has a higher bed utilization rate and a longer effective operating cycle.
[0063] The pressure drop of the fixed-bed adsorption column was 8.6 kPa, 9.4 kPa, and 8.9 kPa in Examples 1-3, respectively, which was lower than that of Comparative Example 1 (13.8 kPa), Comparative Example 2 (15.6 kPa), and Comparative Example 3 (12.4 kPa). This indicates that the cerium-based metal-organic framework-derived cerium-oxygen cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets improved the bed permeability and anti-clogging ability, and reduced energy consumption and maintenance pressure during continuous operation.
[0064] After the 10th cycle, the alkali recovery rates of Examples 1-3 remained at 92.8%, 89.6%, and 91.1%, respectively, while those of Comparative Examples 1-3 decreased to 79.4%, 73.8%, and 83.2%, respectively. This indicates that the cerium-based metal-organic framework-derived cerium-oxygen cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets in Examples 1-3 can still maintain high recovery capacity after reverse rinsing with water, desorption with sodium hydroxide solution, and rinsing with water. This solves the problems of poor cycle stability, decreased adsorption efficiency after regeneration, and unstable quality of recovered alkali solution in traditional adsorption materials in strongly alkaline dyeing and finishing waste liquid.
Claims
1. A method for alkali recovery in a dyeing and finishing workshop, characterized in that, Includes the following steps: S1. The dyeing and finishing waste alkaline solution is filtered through a grid and a vibrating screen to obtain the filtered dyeing and finishing waste alkaline solution. The filtered dyeing and finishing waste alkaline solution is filtered through a multi-media filter to obtain pre-filtered dyeing and finishing waste alkaline solution. S2. The pre-filtered dyeing and finishing waste alkaline liquid is pumped into a fixed bed adsorption column filled with cerium-based metal-organic framework-derived cerium-oxygen clusters supported on niobate-functionalized mesoporous titanium dioxide composite nanosheets. The pre-filtered dyeing and finishing waste alkaline liquid enters from the top of the fixed bed adsorption column and flows out from the bottom, thus obtaining the recovered alkaline liquid after adsorption treatment. S3. When the color of the effluent from the fixed bed adsorption column is greater than 30 degrees or the COD removal rate drops to below 85% of the initial COD removal rate, stop feeding the pre-filtered dyeing and finishing waste alkaline solution; first, rinse the fixed bed adsorption column with clean water in a reverse direction, then desorb it with a 2-5% sodium hydroxide solution at 50-60℃; finally, rinse the fixed bed adsorption column with clean water. S4. Measure the sodium hydroxide concentration in the recovered alkali solution after adsorption treatment. If the sodium hydroxide concentration is lower than the target process requirement, the recovered alkali solution is concentrated by negative pressure evaporation to obtain the adjusted recovered alkali solution. If the sodium hydroxide concentration is higher than the target process requirement, the recovered alkali solution is diluted to obtain the adjusted recovered alkali solution.
2. The method for alkali recovery in a dyeing and finishing workshop according to claim 1, characterized in that, In step S1, the multi-media filter is filled with quartz sand, anthracite, and manganese sand.
3. The method for alkali recovery in a dyeing and finishing workshop according to claim 1, characterized in that, In step S2, the cerium-based metal-organic framework-derived cerium-oxygen cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets are activated in a vacuum drying oven at 80-100℃ for 4-8 hours, and then packed into a fixed-bed adsorption column.
4. The method for alkali recovery in a dyeing and finishing workshop according to claim 1, characterized in that, In step S3, the desorption time is 60-120 minutes.
5. The method for alkali recovery in a dyeing and finishing workshop according to claim 1, characterized in that, In step S3, after desorption, the fixed bed adsorption column is rinsed with clean water for 30-60 minutes.
6. The method for alkali recovery in a dyeing and finishing workshop according to any one of claims 1-5, characterized in that, The preparation steps of the cerium-based metal-organic framework-derived cerium oxide cluster-supported niobate-functionalized mesoporous titanium dioxide composite nanosheets include: A1. By weight, under nitrogen protection, mix 10-15 parts of cerium nitrate hexahydrate, 120-180 parts of N,N-dimethylformamide, and 40-70 parts of glacial acetic acid, and stir at room temperature to obtain a cerium-containing precursor solution; mix 5.5-9.5 parts of 2,2′-bipyridine-5,5′-dicarboxylic acid, 60-100 parts of N,N-dimethylformamide, and 20-40 parts of glacial acetic acid, and stir at room temperature to obtain a ligand dispersion; add the ligand dispersion dropwise to the cerium-containing precursor solution, and continue stirring at room temperature to obtain a premix; A2. Transfer the premixed solution to an autoclave and stir. After sealing the autoclave, heat it to 120-135℃ for reaction, and then cool it naturally to room temperature to obtain the reaction product. Centrifuge the reaction product to obtain the precipitate. Wash the precipitate sequentially with N,N-dimethylformamide, anhydrous ethanol and deionized water, and vacuum dry it to obtain the cerium-based metal-organic framework material. A3. Mix 2.0-4.0 parts of P123 and 80-120 parts of anhydrous ethanol and stir; add 3-8 parts of hydrochloric acid solution to adjust the pH to 1.5-2.5; add 15-25 parts of tetrabutyl titanate and stir to obtain titanium sol; dissolve 1.0-3.0 parts of ammonium niobate oxalate in 20-40 parts of deionized water to obtain niobium source solution; add the niobium source solution to the titanium sol and stir to obtain mixed sol; transfer the mixed sol to an autoclave, heat to 140-170℃ for reaction, and then cool naturally to room temperature to obtain reaction product; centrifuge the reaction product to obtain precipitate; wash the precipitate successively with deionized water and anhydrous ethanol, vacuum dry, and calcine in air at 400-500℃ to obtain niobate-functionalized mesoporous titanium dioxide nanosheets; A4. Mix 5-10 parts of cerium-based metal-organic framework material, 10-30 parts of niobate-functionalized mesoporous titanium dioxide nanosheets, and 150-250 parts of anhydrous ethanol, stir at room temperature, and ultrasonically disperse. Add 0.5-1.5 parts of 3-aminopropyltriethoxysilane and 1-7.5 parts of deionized water, and reflux at 75-85℃ to obtain the reaction product. Centrifuge the reaction product to obtain a solid product. Wash the solid product sequentially with anhydrous ethanol and deionized water, and vacuum dry to obtain a vacuum-dried solid product. Place the vacuum-dried solid product in a tube furnace and heat-treat at 400-500℃ under a nitrogen atmosphere. Allow to cool naturally to room temperature.
7. The method for alkali recovery in a dyeing and finishing workshop according to claim 6, characterized in that, In step A1, after the ligand dispersion is added dropwise to the cerium-containing precursor solution, the mixture is stirred at room temperature for 6-8 hours.
8. The method for alkali recovery in a dyeing and finishing workshop according to claim 6, characterized in that, In step A2, the reaction time is 36-48 hours after heating to 120-135℃.
9. The method for alkali recovery in a dyeing and finishing workshop according to claim 6, characterized in that, In step A3, the reaction time is 24-36 hours after heating to 140-170℃.
10. The method for alkali recovery in a dyeing and finishing workshop according to claim 6, characterized in that, In step A4, the reflux reaction time at 75-85℃ is 12-18 hours.